Prevalence of Depression among Mothers of Children with Cerebral Palsy (CP) Enrolled in Occupational Therapy Unit at Lady Reading Hospital Peshawar, Pakistan : Depression among Mothers of Children with Cerebral Palsy (CP) - Ayub, Ayaz; Rahim, Tariq; Bahadar, Sher; Saleem, Muhammad (Pakistan Journal of Health Sciences, 2023)
Cerebral Palsy (CP) is one of the most prevalent physical disorder in developmental disabilities among children. This condition may prone the parents for development of depression and anxiety especially the mothers. Objective: To assess the prevalence of depression among mothers of children with CP in Peshawar, Pakistan. Methods: A descriptive cross sectional study was conducted prior to randomize control trials in Occupational Therapy Department of Lady Reading Hospital Peshawar. The sample was calculated through Openepi, consisted of 240 participants through consecutive sampling technique. The quantitative data were collected through Hospital Anxiety and Depression (HADS) scale from mothers whose score was greater than 3 on the general health questionnaire (GHQ-12). Results: The mean age of the participants was 31.63± 7.09 years. In a sample of 240 participants, married were 230 participants followed by 6 divorced and 4 widows. Furthermore, 58% participants have male children affected followed by 42% female children. The mean score of the participants’ depression was 12.49 ± 3.18 in a total score of 21, which was moderate to severe in the current study. Conclusions: The study concluded that mothers of CP child have moderate to severe level of depression. Furthermore, the study highlighted that majority of the participants were married and the prevalence rate of CP was higher male children as compared to female.